(untitled) (Western Pacific Surveillance and Response, 2019)
We conducted ad-hoc event screening and risk assessment of public health events during the 2018 Pyongchang Olympic-Paralympic Winter Games from the perspective of a non-host country. In this report, we described the process of our experiences and the lessons learned.